Removable Partial Denture with dual path of insertion: clinical case report - Eduardo Shigueyuki Uemura; João Mauricio Ferraz da Silva; Alberto Noriyuki Kojima; Carlos Rocha Gomes Torres; Cleiton Santos Vieira (Brazilian Dental Science)
Removable Partial Dentures (RPD) with dual path of insertion are designed to overcome conventional RPD esthetic limitations, through the use of proximal undercuts for rigid direct retainers. Therefore, dual path RPD is considered a variation of conventional RPD. This paper reports a clinical case where proper function as well as excellent esthetics were obtained with this type of RPD.